Creating a Cinema of Boxing in Day of the Fight (Stanley Kubrick, 1951) - Myriam Mellouli (Mise au Point)
Stanley Kubrick's first movie is a boxing film. It is Day of the Fight, a 1951 short documentary on the Irish-American boxer and actor William Walter Cartier. Previously a photographer for Look Magazine (1945-1950), Stanley Kubrick develops in the film his cinematographic style sketched in a photojournalistic report for which he took more than 1200 photographs of William Walter Cartier. This boxing film contributes to the construction of his status as an author and Day of the Fight kicks off his singular aesthetic of violence. As a transitional work between two art forms, photography and cinema, the boxing film allows the unfolding of Stanley Kubrick's fascination for physical confrontation. The young director, inspired by film noir, exploits the transgressive nature of the sport, which has been present since the beginnings of cinema. Beyond the supposed violence of boxing, Day of the Fight captures the male body and the intimacy of the boxer through a non-conformist homoerotic gaze.